Tutankhamun - Bommas, Martin, author.
1 online resource.
Keywords: "Over a century after his discovery, this comprehensive biography of Tutankhamun explores a wealth of evidence, including archaeological and ancient textual sources, DNA analysis, and CT scanning, bringing to life a pharaoh who has remained elusive apart from his grandiose tomb treasures. For the first time, this volume identifies the names of Tutankhamun's biological parents, tracing the footsteps of his short life that was marked by genetic defects and physical deterioration. Between his early days and his untimely death, Tutankhamun (previously Tutankhaten) appears as a child of his time; he was torn between the cult of the Aten and the restoration of the cult of Amun, a campaign in which he personally played a leading role. Equipped with a thorough education, gifted with a brilliant mind, and living mostly in solitude, readers will follow in detail how Tutankhamun secured the survival of the 18th Dynasty. This book traces Tutankhamun's involvement in processes which can still be felt in Egypt today. His complex personality is reconstructed based on archaeological evidence - some of which has never been discussed previously - and conclusions drawn from both scientific research and a deep understanding of the context in which he lived. By also considering the lives of those who were close to the teenage king, this book delivers a comprehensive source-based biography of an ancient Egyptian pharaoh. Complete with intensive references to international scholarship, visual sources, and maps, and excluding the tomb treasures created after his physical death, this book is a fresh and original approach to understanding the life - not afterlife - of the most popular pharaoh of modern times. Tutankhamun: A Biography is suitable for students, scholars, and non-specialist readers interested in the life of Tutankhamun, as well as those working on ancient Egyptian history and religion more broadly, particularly that of New Kingdom Egypt"--